Ethics in Osteopathic practice and research: the proposal for an Ethical Framework - Ferioli, Elena (Medicina Historica, 2022)
Actually the clinical and research context in which health care is provided is characterized by new challenges for health workers, researchers and the broader health care of the community who increasingly find themselves confronted with moral questions and ethical dilemmas which are not rare phenomena and thus merit special attention. Clinical ethics is a thoughtful exploration of how to act well and make morally good choices, based on beliefs and values about life, health, suffering, and death. Because of their holistic approach to medicine and as predominantly primary care practitioners, osteopaths may face a wide range of ethical dilemmas. Recently the National Council for Osteopathic Research has produced a document intended to demonstrate best practice in osteopathic research that must be considered when conducting research in an ethical manner. On the other hand, actually, substantive discussion of specific ethical issues is rarely included in clinical research protocols. A framework of ethics analysis geared specifically for osteopaths is needed to highlight the values morally relevant in their clinical and research practice. A preliminary attempt at such a framework is offered in this study with the development of an ethical framework and two practical ethics tool kits serviceable for clinical and research practice perfectly fitted for osteopathic profession.